Pharmacokinetics and Safety of Eszopiclone in Healthy Chinese Volunteers - Wu, F.; Zhao, X. L.; Wei, M. J.; Wang, S. M.; Zhou, H.; Guo, S. J.; Zhang, P. (Arzneimittelforschung, 2012)
The main objective of this study was to investigate the pharmacokinetic characters of eszopiclone (CAS: 138729-47-2) after single and multiple-dose oral administration in healthy adult Chinese volunteers.In single-dose study, 12 subjects were given oral administrations of 1.5, 3 and 6 mg eszopiclone in an open-label, randomized, crossover fashion. In multiple-dose study, 8 subjects were given 3 mg eszopiclone once daily consecutively for 7 days. Blood samples were collected over 24 h and plasma eszopiclone were determined using a validated liquid chromatography/mass spectrometry (LC/MS/MS) assay. The safety and tolerability of eszopiclone was evaluated by adverse events recording, physical examination, laboratory testing, vital signs, and 12-lead ECG findings.The main pharmacokinetic parameters of eszopiclone after single-dose administration were as follows: doses of 1.5, 3 and 6 mg; Cmax of 18.08±4.65, 38.29±15.41 and 76.38±23.34 ng/ml; Tmax of 0.94±0.39, 1.04±0.63 and 1.08±0.51 h; AUC0–24 of 110.90±23.06, 227.36±62.41 and 504.10±140.13 ng*h/ml; elimination half-lives of 5.84±1.03, 5.53±1.91 and 6.17±1.23 h. After multiple-dose administration, the steady-state levels of eszopiclone were achieved by the 4th day, and the main pharmacokinetic parameters were Css_max at 33.43±5.63 ng/ml and AUCss (0–24) at 263.30±51.21 ng*h/ml. The most common adverse event was bitter or abnormal taste. All the adverse events were judged as mild to moderate and resolved without any medication.The pharmacokinetic character of eszopiclone is linear and dose-proportional over the range of 1.5–6 mg. The systemic exposure does not accumulate with once-daily administrations. Eszopiclone appears to have good safety and is well tolerated.
Keywords: eszopiclone; pharmacokinetics; safety; tolerability